Interrogating the Norm: The Dilemma of Marriage in KaveriNambisan’s Mango- Coloured Fish - G, Prasanth V; Viswanathan, Vidhya (International Journal of Psychosocial Rehabilitation, 2020)
Feminists over the years have brought to the forefront those silenced aspects related to the predicament of women in a patriarchal society. Critics and theorists including Simone de Beauvoir, Mary Wollstonecraft, Julia Kristeva, Helene Cixous, Luce Irigaray, Kate Millet and Elaine Showalter have discussed and debated on the marginalization of women, their quagmire in patriarchal society and spatial justice with respect to women across the globe. In spite of all the discourses ongenderequality and justice, true feminine experiences and expressions are still smothered by both matriarchy and patriarchy. In this context, the present paper makes an attempt to analyze the suppressed voices, questions and uncertainties that rise in the mind of the protagonist in KaveriNambisan’s novel, Mango-ColouredFishfrom a feminist perspective.The concept of marriage and its aftermath are analyzed within the framework of feminism and patriarchy with the respect to the selected novel.